A Novel Method for Administering Epinephrine during Neonatal Resuscitation - Gu, Hannah; Perl, Juliana; Rhine, William; Yamada, Nicole K.; Sherman, Jules; McMillin, Alexandra; Halamek, Louis P.; Wall, James K.; Fuerch, Janene H. (American Journal of Perinatology, 2023)
Objective This study aimed to determine if prefilled epinephrine syringes will reduce time to epinephrine administration compared with conventional epinephrine during standardized simulated neonatal resuscitation.Study Design Timely and accurate epinephrine administration during neonatal resuscitation is lifesaving in bradycardic infants. Current epinephrine preparation is inefficient and error-prone. For other emergency use drugs, prefilled medication syringes have decreased error and administration time. Twenty-one neonatal intensive care unit nurses were enrolled. Each subject engaged in four simulated neonatal resuscitation scenarios involving term or preterm manikins using conventional epinephrine or novel prefilled epinephrine syringes specified for patient weight and administration route. All scenarios were video-recorded. Two investigators analyzed video recordings for time to epinephrine preparation and administration. Differences between conventional and novel techniques were evaluated using the Wilcoxon Signed Rank Tests.Results Twenty-one subjects completed 42 scenarios with conventional epinephrine and 42 scenarios with novel prefilled syringes. Epinephrine preparation was faster using novel prefilled epinephrine syringes (median = 17.0 s, interquartile range [IQR] = 13.3–22.8) compared with conventional epinephrine (median = 48.0 s, IQR = 40.5–54.9, n = 42, z = 5.64, p < 0.001). Epinephrine administration was also faster using novel prefilled epinephrine syringes (median = 26.9 s, IQR = 22.1–33.2) compared with conventional epinephrine (median = 57.6 s, IQR = 48.8–66.8, n = 42, z = 5.63, p < 0.001). In a poststudy survey, all subjects supported the clinical adoption of prefilled epinephrine syringes.Conclusion During simulated neonatal resuscitation, epinephrine preparation and administration are faster using novel prefilled epinephrine syringes, which may hasten return of spontaneous circulation and be lifesaving for bradycardic neonates in clinical practice.Key Points
Keywords: neonatal resuscitation; epinephrine; simulation; prefilled medication syringes